Influence of naa on growth, yield attributes and yield of brri dhan-48 (Oryza Sativa L.) (Bangladesh Journal of Botany, 2025)
A pot experiment was conducted to investigate the influence of NAA (0, 20, 40, 60, 80 and 100 ppm) on growth, yield attributes and yield of BRRI Dhan-48. Results showed that NAA had stimulatory effects on growth parameters where better influences were noted from higher concentration. Application of 100 ppm NAA had produced the tallest plant, maximum number of leaves, dry weight of root, leaf area per plant and leaf area duration all over the growth ages with few exceptions. The highest number of tillers per plant was obtained from 40 ppm NAA.  Foliar application of 60 ppm NAA had resulted higher dry weight of shoot and biomass duration at early stages whereas, in case of net assimilation rate 80 ppm produced better responses. Yield attributes and yield of BRRI Dhan-48 was positively influenced by different concentration of NAA with few exceptions. Number of effective tillers per plant (7.63), dry weight of panicles per plant (2.99g), number of grains per panicle (88.94), percentage of filled grains (99.16), yield per plant (3.57g) and harvest index (13.24%) were obtained maximum from 40 ppm treatments. The longest length of panicle (24.64 cm) produced by 80 ppm NAA and highest 1000-grain weight (13.51g) by 60 ppm NAA were statistically similar to 40 ppm NAA treatments. Results also revealed that 40 ppm NAA produced significantly higher yield and was 67.61% over the control. Out of six treatments, 40 ppm NAA is the best option for obtaining higher yield. Bangladesh J. Bot. 54(2): 285-291, 2025 (June)